Technologies used in Supply Chain Management in Romania: where is it going? - Elena PUICA (Dunarea de Jos University of Galati, 2021)
In this paper are analysed the tendencies in innovation for supply chain management in Romania through different industries and multiple aspects of use of the technologies. Research findings show a prediction of how much the technologies are used in the next year by different enterprises from different industries in Romania. The findings of the research, ware determined by applying a forecast model based on historical database from almost 4 years ago. The research paper is contributing with new insights in the SCM market in Romania, being a starting point in in the field of studies comprehending a better understanding of technologies used in Romania in SCM.